Natural selection in wild beetle populations - Wendel,Erik (2024)
Natural selection is an important force behind evolution. It is well known that phenotypic variation provides opportunity for evolution, but research into how selection acts on specific traits over time is lacking. In this thesis, I studied how selection acts upon the shape and body size of the beetle Cassida viridis. Across three populations, I measured size (length and area), shape, and lifespan in two generations of beetles. In addition, I experimentally assessed predation likelihood in the three populations. Using these data, I modeled the differences across populations to determine if selection is acting on these traits. I found that there was disruptive selection on length in the first generation and shape in the second generation across all three populations, potentially due to predation, intraspecific competition, and a tendency for negative directional selection on size. There were also significant differences in survival across populations. However, I observed no correlation between predation intensity and survival. My results suggest that survival may be correlated with the timing of diapause, which may help us understand why insects enter diapause at certain times. This study is the first to explore how natural selection shapes the body size of C. viridis among populations and suggests that C. viridis has proven to be a useful study system to answer questions about how selection shapes populations. Future studies would benefit from including measurements of sexual selection and following the same individuals or generations across their lifecycle.